2022
DOI: 10.1021/acscentsci.1c01548
|View full text |Cite
|
Sign up to set email alerts
|

Structural–Energetic Basis for Coupling between Equilibrium Fluctuations and Phosphorylation in a Protein Native Ensemble

Abstract: The functioning of proteins is intimately tied to their fluctuations in the native ensemble. The structural–energetic features that determine fluctuation amplitudes and hence the shape of the underlying landscape, which in turn determine the magnitude of the functional output, are often confounded by multiple variables. Here, we employ the FF1 domain from human p190A RhoGAP protein as a model system to uncover the molecular basis for phosphorylation of a buried tyrosine, which is crucial to the transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Phosphorylation depletes the population of the metastable state thereby shifting the (natively folded state ↔ metastable state) equilibrium toward the right, eventually facilitating the phosphorylation of the entire population of natively folded HipA. This model is consistent with similar mechanisms proposed in a number of recent studies on the phosphorylation of buried amino acids. …”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Phosphorylation depletes the population of the metastable state thereby shifting the (natively folded state ↔ metastable state) equilibrium toward the right, eventually facilitating the phosphorylation of the entire population of natively folded HipA. This model is consistent with similar mechanisms proposed in a number of recent studies on the phosphorylation of buried amino acids. …”
Section: Introductionsupporting
confidence: 87%
“…Similarly, it was reported that the transient exposure of a buried Tyr in the acidic inhibitory domain allows it to be phosphorylated, leading to the inhibition of the Dbl homology domain in the protein Vav1 . The FF1 domain from the human p190A RhoGAP protein was shown to be present as an ensemble of conformations, some of which are phosphorylation-competent . Therefore, transient surface exposure may be a general mechanism of phosphorylation of buried residues in proteins.…”
Section: Conclusion and Perspectivementioning
confidence: 89%
See 1 more Smart Citation
“…57 Remarkably, a surface lysine in FF1 from the p190A RhoGAP protein controls the extent of structural opening events that determine the phosphorylation of a buried tyrosine. 58 Similarly, electrostatic interactions at the subunit interface of calmodulin, 59 lipoxygenase, 60 pyruvate kinase, 61 DnaK, 62 and aminopeptidease 63 control the ligand binding and activity, despite the salt bridges located far from the functional site. Taken together with the current work, it appears that modulating the strength of interdomain interactions via salt bridges could be a simple avenue to control long-range activity.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The relationship between folding and function has been examined by comparing the free-energy landscapes of homologous proteins with those of proteins with amino-acid substitutions or chemical modifications [ 62 , 63 , 74 , 80 , 87 , 88 , 89 , 90 , 91 , 92 ]. The charge distribution on the protein surface is one of the key factors controlling ligand binding and can also affect protein stability and folding [ 62 , 63 , 74 ].…”
Section: Prediction Of Folding Mechanismsmentioning
confidence: 99%